The Determinant of Loan Portfolio Shifting: Empirical Study of Banks in ASEAN Country - Foza Hadyu Hasanatina; I Wayan Nuka Lantara; Afina Hasya (Jurnal Manajemen Universitas Bung Hatta, 2023)
In offering a loan, banks have several considerations. This is because Standard Basel has regulations and requirements for banks to offer loans. This relates to the bank’s minimum capital and liquidity requirements. This factor includes external and internal factors. This is important to be noted because external and internal factors contain risks inherent in financial instruments. Risk management is one of the things that the executive is most concerned about in taking a policy. Risks faced by the bank include interest rate risk and credit risk. In this case, we study interest rate and credit risk in the bank’s loan offering management role. We study banks in ASEAN Countries. The results show that interest rate is one of the considerations of banks for providing the loan. But, no evidence of credit risk. We also add analysis using a profitability ratio that captures the bank’s loan offering management. In this case, profitability strengthens the model relationship tested.   This title was found in another journal. The journal's editorial team has stated that the title not publish in their journal. https://bit.ly/3EKML08